A feasibility study on the SphygWatch an integration of a digital sphygmomanometer and a wristwatch - Barrios, Maria Andrea; Fabrero, Althea; Lindogan, Rachelle Pearl; Nabong, Jennilyn (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
Hypertension is a condition where the blood pressure elevates. It is experienced when the heart pumps harder to supply the blood that circulates throughout the body. Hypertension has been one of the leading causes of deaths in the Philippines for decades. An estimate of 12.1 million Filipinos are hypertensive. However, half of these people are not even aware that they have this condition. One of the reasons why many people fail to get away from the catastrophe caused by hypertension is that this condition has minimal or no symptoms at all. Furthermore, a hypertensive person will always be hypertemsive unless proper precautions are taken. The treatment for this condition is aimed at maintaining regular blood pressure level through continuous monitoring and lifestyle modification. This paper talk about Sphygwatch: an integration of digital sphygmomanometer in a wristwatch. The main purpose of the sphygwatch is to help people maintain normal blood pressure through regular monitoring. Being aware of one's BP level is the first step in fighting this condition. It leads to the modification of lifestyle towards healthier living which is the only cure to prevent the mishaps caused by hypertension. The market for the Sphygwatch was determined to be Filipinos aged 15 and above from income classes A, B and C, with or without high blood condition. Although there is potential for this product in the global market, marketing efforts with be concentrated towards capturing the said target market. The Sphygwatch's parts arethe main mechanism, bracelet, battery, sensor, bezel and watch box. The product also includes an instruction manual which will guide the user in operating and maintaining the Sphygwatch. The main mechanism will be outsourced but the assembly of the parts will be done in the production and distribution center to be located in Mandaluyong City. The company will be call Sphygwatch Inc., with twenty employees divided into four departments: the marketing and sales Department, Technical Operations Department, Finance Department and Human Resources and Administrative Department. Aside from the direct benefits from the Sphygwatch, the company will also provide jobs for Filipinos. The company will also disburse for its tax obligations to be paid to the government. Futhermore, the healthcare industry will also be improved especially now that there is a ban for mercury sphygmomanometers. The huge impact of the Sphygwatch to the Filipinos was the initial rationale in the pursuance of this project. After a thorough research and investigation of the other aspects of the project as a business, it can be concluded that the development of the Sphygwatch is very much feasible.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Wrist watches; Feasibility studies